The Urgency of Contemporary Fiqh Muamalah in Addressing Modern Socio-Economic Problems - Yusriadi Yusriadi; Nazaruddin Nazaruddin; Alfitra Safarna (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2025)
The development of science demands the actualization of humanity in various aspects of life. The most obvious impact of this modernization is the emergence and growth of various new problems, especially within the scope of Islamic law. Often, the various problems we face require us to seek solutions from a Muslim perspective. In response to these disappointments, contemporary fiqh has emerged as a discipline worthy of in-depth study. This paper contains an explanation of the implicit form of contemporary fiqh, both in terms of its meaning, object, and field of study, the differences between contemporary fiqh and fiqh fiqh, and the importance of studying contemporary fiqh for every Muslim. The research technique used is documentary research with a descriptive and clear background, with the aim of explaining the study precisely and in-depth. The conclusion of this study is that contemporary fiqh (Islamic jurisprudence) is a problem in Islamic law that exists in the current or contemporary era and was not encountered in the era of the Prophet Muhammad or his companions. Therefore, its legal status must be determined through the ijtihad process of mujtahids, referring to fundamental sources of Islamic law, such as the Quran, hadith, and others.